Cytarabine dose of 36 g/m2 compared with 12 g/m2 within first consolidation in acute myeloid leukemia: results of patients enrolled onto the prospective randomized AML96 study - Schaich, Markus; Röllig, Christoph; Soucek, Silke; Kramer, Michael; Thiede, Christian; Mohr, Brigitte; Oelschlaegel, Uta; Schmitz, Norbert; Stuhlmann, Reingard; Wandt, Hannes; Schäfer-Eckart, Kerstin; Aulitzky, Walter; et al. (Journal of clinical oncology, 2011)
Purpose - - To assess the optimal cumulative dose of cytarabine for treatment of young adults with acute myeloid leukemia (AML) within a prospective multicenter treatment trial. - - Patients and Methods - - Between 1996 and 2003, 933 patients (median age, 47 years; range 15 to 60 years) with untreated AML were randomly assigned at diagnosis to receive cytarabine within the first consolidation therapy at either a intermediate-dose of 12 g/m2 (I-MAC) or a high-dose of 36 g/m2 (H-MAC) combined with mitoxantrone. Autologous hematopoietic stem-cell transplantation or intermediate-dose cytarabine (10 g/m2) were offered as second consolidation. Patients with a matched donor could receive an allogeneic transplantation in a risk-adapted manner. - - Results - - After double induction therapy including intermediate-dose cytarabine (10 g/m2), mitoxantrone, etoposide, and amsacrine, complete remission was achieved in 66% of patients. In the primary efficacy analysis population, a consolidation with either I-MAC or H-MAC did not result in significant differences in the 5-year overall (30% v 33%; P = .77) or disease-free survival (37% v 38%; P = .86) according to the intention-to-treat analysis. Besides a prolongation of neutropenia and higher transfusion demands in the H-MAC arm, rates of serious adverse events were comparable in the two groups. - - Conclusion - - In young adults with AML receiving intermediate-dose cytarabine induction, intensification of the cytarabine dose beyond 12 g/m2 within first consolidation did not improve treatment outcome.
Im Titel ist die Zahl 2 jeweils hochgestellt
Gesehen am 07.10.2022